Development of E-LKPD in Differentiated Learning to Improve Students’ Mathematical Communication Skills - Widya Wahyuni Gusti; Sofnidar; Ade Kumalasari (Riemann: Research of Mathematics and Mathematics Education, 2024)
This research aims to describe the development process and quality of web-assisted E-LKPD in differentiated learning based on learning styles with a problem-based learning model to improve junior high school students' mathematical communication skills in terms of the validity of the E-LKPD, practicality, and effectiveness. This research was conducted in class VII of SMP Negeri 14 Jambi City. The method used in this research is Research and Development using the ADDIE model. Where the results of this research come from the percentage of material validation of 91% in the "very valid" category, the percentage of design validation of 88% in the "very valid" category, the percentage of practicality by teachers of 96% in the "very practical" category, the percentage of practicality by students of 89 % categorized as "very practical", the percentage of effectiveness by students was 91.25% categorized as "very effective" and the calculation of the gain value in improving students' mathematical communication skills was 76% categorized as "quite effective".